[Men on a boat] - (:unkn) unknown (Unknown, 2011)
The postcard shows some men being transported by a small boat.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Boats and boating; Men; Hats; Sheds; Transportation